Dynamical Study of a Predator-Prey Model Including Allee Effect, Prey Group Defence, and Extra Food for the Predators - Ramesh, B.; Ramesh, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
The paper introduces a prey-predator scheme which involves the Allee effect and prey group defence, two important ecological phenomena that can coexist. Also, we let generalist predators have access to a different food source, which modifies their carrying capacity. Near the equilibrium points, we thoroughly examine the qualitative behaviours of the suggested model. The model is refined to better capture real-world predator-prey dynamics by integrating the Allee effect and collective defense mechanisms. Research into stability criteria, bifurcation events, and equilibrium points helps fill gaps in our understanding of ecological system dynamics. This work highlights the significance of considering intricate connections when simulating ecosystems, particularly in relation to predator-prey dynamics. To deepen our understanding of these systems, future research may investigate additional ecological factors. Finally, our study contributes to ecological modelling by elucidating key dynamics and providing insights into predator-prey system behaviour in different contexts. This study provides a comprehensive analysis of the model to improve our understanding of ecological systems with complex interdependencies, focussing on how the Allee effect in prey and extra food for predators affect the system dynamics.